Neural Development - Schatten, Gerald; ScienceDirect eBooks (Amsterdam : Elsevier, 2005)
Current Topics in Developmental Biology provides a comprehensive survey of the major topics in the field of developmental biology. The volumes are valuable to researchers in animal and plant development, as well as to students and professionals who want an introduction to cellular and molecular mechanisms of development. The series has recently passed its 30-year mark, making it the longest-running forum for contemporary issues in developmental biology. Neural Development, the most recent publication in the series, covers the most up-to-date discoveries and developments of the brain. This volume touches upon topics such as the fly retina, telencephalon development, glia-neuron interactions in the nervous system, midbrain and cerebellum development, synapse formation from visual behavior screens, the role of MEF2 proteins, and much more. * Over 35 tables and figures in full color with detailed illustrations * Includes 10 riveting chapters of the most recent discoveries in neural development * Discusses such topics as the role of glial cells, susceptibility of damage to the brain, the developing visual cortex and much more.
Text in English.
Online resource; title from HTML table of contents page (ScienceDirect, viewed Sept. 30, 2013).
Elsevier
Keywords: Nervous system -- Growth; Developmental Biology; Regenerative Medicine; Nervous System -- growth & development; Nervous System -- embryology; Nervous system -- Growth; Neuronen; Zenuwstelsel; Ontwikkelingsbiologie; Nervensystem; Entwicklung; Electronic books